Increased 30-Day Mortality Risk in Patients With Diabetes Mellitus After Colon Cancer Surgery: A Mediation Analysis. Issue 3 (March 2020) - Schootman, Mario; Jeffe, Donna B.; Ratnapradipa, Kendra L.; Eberth, Jan M.; Davidson, Nicholas O.
Abstract : BACKGROUND: Patients with (versus without) diabetes mellitus who develop colon cancer are at increased risk of dying within 30 days after surgery. OBJECTIVE: The purpose of this study was to identify potential mediators of the effect of diabetes mellitus on all-cause 30-day mortality risk after surgery for colon cancer. DESIGN: A retrospective cohort study was conducted using the 2013–2015 National Surgical Quality Improvement Program data. SETTING: The study was conducted at various hospitals across the United States (from 435 to 603 hospitals). PATIENTS: Patients who underwent resection for colon cancer with or without obstruction based on the National Surgical Quality Improvement Program colectomy module were included. Patients who had ASA physical status classification V or metastatic disease and those who presented emergently were excluded. Patients were classified as "no diabetes, " "diabetes not requiring insulin, " or "diabetes requiring insulin." Potential reasons for increased risk of dying within 30 days were treatment related, comorbidity, health behaviors, surgical complications, and biomarkers of underlying disease. MAIN OUTCOME MEASURES: We measured all-cause 30-day mortality. RESULTS: Of 26, 060 patients, 18.8% (n = 4905) had diabetes mellitus that was treated with insulin (n = 1595) or other antidiabetic agents (n = 3340). Patients with diabetes mellitus had a 1.57 (95% CI, 1.23–1.99) higher unadjusted odds of dying within 30 days versus patients without diabetes mellitus. In the multivariable model, 76.7% of the association between diabetes mellitus and 30-day mortality was explained; patients with diabetes mellitus were equally likely to die within 30 days versus those without diabetes mellitus (OR = 1.05 (95% CI, 0.81–1.35)). Anemia and sepsis explained 33.7% and 15.2% of the effect of diabetes mellitus on 30-day mortality (each p < 0.0001). Treatment-related variables, cardiovascular disease, surgical complications, and biomarkers played limited roles as mediators. LIMITATIONS: The study was limited to larger hospitals, and limited information about duration and type of diabetes mellitus was available. CONCLUSIONS: Better management and prevention of anemia and sepsis among patients with diabetes mellitus may reduce their increased risk of death after colon cancer resection. See Video Abstract at http://links.lww.com/DCR/B140 . AUMENTO DEL RIESGO DE MORTALIDAD A 30 DÍAS EN PACIENTES DIABETICOS LUEGO DE CIRUGÍA DE CÁNCER DE COLON: ANÁLISIS DE MEDIACIÓN: ANTECEDENTES: Los pacientes con (y sin) diabetes que desarrollan cáncer de colon tienen un mayor riesgo de morir dentro de los 30 días posteriores a la cirugía. OBJETIVO: Identificar los posibles mediadores del efecto de la diabetes sobre el riesgo de mortalidad dentro los 30 días, por cualquier causa después de cirugía por cáncer de colon. DISEÑO: Estudio de cohortes retrospectivo entre 2013-2015 utilizando los datos del Programa Nacional de Mejoría en Calidad Quirúrgica. AJUSTE: Entre 435 a 603 hospitales en los Estados Unidos. PACIENTES: Se incluyeron aquellos pacientes sometidos a resección por cáncer de colon con o sin obstrucción según el módulo de colectomía Programa Nacional de Mejoría en Calidad Quirúrgica. Se excluyeron los pacientes estadío V de la clasificación de la Sociedad Estadounidense de Anestesiólogos (ASA), aquellos con enfermedad metastásica y aquellos operados de urgencia. Los pacientes se clasificaron como "sin diabetes, " "con diabetes que no requiere insulina" o "con diabetes que requiere insulina." Las posibles razones para un mayor riesgo de morir dentro de los 30 días estuvieron relacionadas con el tratamiento, la comorbilidad, los comportamientos de salud, las complicaciones quirúrgicas y los biomarcadores de enfermedad. PRINCIPALES RESULTADOS: Mortalidad de cualquier orígen dentro los 30 días depués de la cirugía. RESULTADOS: De 26'060 pacientes, 18.8% (n = 4, 905) tenían diabetes tratada con insulina (n = 1, 595) u otros agentes antidiabéticos (n = 3, 340). Los pacientes con diabetes tenían 1.57 (IC 95%: 1.23-1.99) mayores probabilidades no ajustadas de morir dentro de los 30 días en comparación con los pacientes sin diabetes. En el modelo multivariable, se explicó que el 76, 7% de la asociación entre diabetes y mortalidad a los 30 días; los pacientes con diabetes tenían la misma probabilidad de morir dentro de los 30 días que aquellos sin diabetes (OR: 1.05; IC 95%: 0.81-1.35). La anemia y la sepsis explicaron el 33, 7% y el 15, 2% del efecto de la diabetes en la mortandad a 30 días (p <0, 0001). Las variables relacionadas con el tratamiento, las enfermedades cardiovasculares, las complicaciones quirúrgicas y los biomarcadores jugaron un papel limitado como mediadores. LIMITACIONES: Estudio limitado a hospitales más grandes e información limitada sobre la duración y el tipo de diabetes. CONCLUSIONES: Una mejor prevención y manejo de la anemia y la sepsis en los pacientes con diabetes puede reducir el mayor riesgo de muerte después de la resección del cáncer de colon. Consulte Video Resumen en http://links.lww.com/DCR/B140 .